The Influence Quantum Learning Model To Critical Thinking Ability (Faculty of Teacher Training and Education, Universitas Terbuka, 2020)
The problem in this study was the low skill of students' critical thinking, especially in the subjects of natural science. This is due to the limited learning model used by a teacher in schools. Preliminary observations by researchers have shown that teachers still use conventional learning models. This research is to know the difference of critical thinking ability of students who implement quantum learning model with the critical thinking ability of students who do not apply the quantum learning of fifth-grade students in natural science subjects at Warungbambu III Elementary School East Karawang. The research methods in this research using a quasi-experimental design with a nonequivalent control group design. The data analysis technique to test hypotheses is done by calculating the statistical independent t-test Samples. Based on the results shows that there are differences in students' critical thinking skills implementing the quantum learning model with the critical thinking skill of students who do not apply the quantum learning model of fifth-grade students in natural science subjects at Warungbambu III Elementary School East Karawang. It is evidenced by the value of sig (2-tailed) 0,000 ? 0.05, which means that the hypothesis is accepted.